Analisis Yuridis Terhadap Perlindungan Hak Kekayaan Intelektual Pada Game Mobile Legend Dan League Of Legend Dalam Perspektif Hukum Indonesia - Muhammad Rafly Badu; Muthia Cherawaty Thalib; Mohamad Taufiq Zulfikar Sarson (Lembaga Pengembangan Kinerja Dosen, 2023)
This research aims to determine the Juridical Analysis of Intellectual Property Rights Protection in the Mobile Legend and League of Legend Games from an Indonesian Legal Perspective, based on the title raised in this research. This research uses a type of normative juridical research. The process of collecting data from the objects studied in this research uses primary, secondary and tertiary techniques. The data obtained by this research uses a qualitative method which explains the relationship between variables and generalizes the social phenomena studied.The results of this research show that online gaming has become a rapidly growing industry with many opportunities and challenges related to intellectual property rights and the development of the online gaming industry has also brought complex issues related to copyright, trademarks and patents involving various elements. unique in online games. therefore, the role of intellectual property rights in protecting creative works in games, encouraging innovation, and overcoming violations of intellectual property rights. So it is important to collaborate between online game developers, players and the government in creating a clear and fair legal framework to protect intellectual property rights in online games.